O futuro da indústria da música no Brasil - Kikko, Vanessa (2012)
The music industry has been facing great changes in the past years. Although the sector has always showed to be very dynamic, especially with the constant rise of new technologies, the current trend seems to be substantially different from the previous ones. The first technologies such as cassettes and vinyl LP’s, started to lose their shares to CD’s when it was introduced in the market in the beginning of the 80’s (PIKAS, PIKAS, & LYMBURNER, 2011). However, the way the business worked, remained the same. The record labels were still the big players in the sector, and did not face any external competition. This scenario changed in the end of the 20th century. MP3 files, which were developed in 1989 but did not reached in large scale the American market until 1999, started to gain more popularity (PIKAS, PIKAS, & LYMBURNER, 2011). With that popularity, also came the illegal online downloading and huge losses to the record labels. Given this dynamic characteristic, the purpose of this work is to analyze not the present or the current trends of this industry, but instead prospect possible future scenarios for the next years in Brazil. In other words, show different possibilities of how the industry can look like in the next years. Thus, this work will use the scenario planning methodology, and interviews with experts in the field to help unfolding these alternative scenarios.